2020
DOI: 10.3390/ijerph17207685
|View full text |Cite
|
Sign up to set email alerts
|

How Can the Lived Environment Support Healthy Ageing? A Spatial Indicators Framework for the Assessment of Age-Friendly Communities

Abstract: The Age-Friendly Cities and Communities Guide was released by the World Health Organization over a decade ago with the aim of creating environments that support healthy ageing. The comprehensive framework includes the domains of outdoor spaces and buildings, transportation, housing, social participation, respect and inclusion, civic participation and employment, communication and information, and community and health services. A major critique of the age-friendly community movement has argued for a more clearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 107 publications
0
25
0
Order By: Relevance
“…This approach has been used to structure community level studies of public health as it relates to early childhood [6,12,13] and family wellbeing [14][15][16], and to design comprehensive models for community action and policy engagement [6,7,10,11]. A human ecological model of public health looks at multiple layers: the community built environment, community level services, public engagement, collaboration among health related agencies, and geographic differences across place [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This approach has been used to structure community level studies of public health as it relates to early childhood [6,12,13] and family wellbeing [14][15][16], and to design comprehensive models for community action and policy engagement [6,7,10,11]. A human ecological model of public health looks at multiple layers: the community built environment, community level services, public engagement, collaboration among health related agencies, and geographic differences across place [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, an alternative approach to measuring Blue Zones ® could consider using quantitative measures by building on the work of Davern and colleagues [ 79 ], whereby employing a Geographic Information Systems (GIS) to measure spatial indicators associated with Blue Zones ® may afford various actors the opportunity to understand the greater importance and associations reflected in the lived environment(s) in an attempt to facilitate and enhance health and wellbeing. In addition to the work published by Davern et al [ 79 ], Jackisch et al [ 80 ] and the United Nations—New Urban Agenda, the 2030 Agenda for Sustainable Development [ 81 ] have also employed GIS techniques and approaches as a means of understanding the impact and importance of spatial indicators associated with age-friendly cities and communities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, research in Australia has shown that Internet access is also becoming increasingly necessary for the elderly to access information about the government, health, banking, and community services [ 20 ]. Moreover, intelligent assistive technologies (IATs) have also been found to be of great help to the Canadian elderly in healthcare, daily life, travel, and communication and is expected to be widely used in the future [ 21 ].…”
Section: Introductionmentioning
confidence: 99%